2021
DOI: 10.1002/rcs.2264
|View full text |Cite
|
Sign up to set email alerts
|

A new robotically assisted system for total knee arthroplasty: A sheep model study

Abstract: Background We investigated the accuracy and safety of a new HURWA robotic‐assisted total knee arthroplasty (TKA) system in a sheep model. Methods Ten male small‐tailed Han sheep were used in this study. Sheep were imaged by computed tomography scan before and after bone resection and the cutting errors between actual bone preparation and preoperative planning of the femur and tibia in three dimensions were measured. Results The overall accuracies after surgery compared with that from preoperative surgical plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our previous studies showed that this new robotic-assisted TKA system significantly improve the accuracy of bone resection levels and angles in the Sawbone model [ 33 ]. Moreover, we demonstrated that this new system is a safe and accurate tool for TKA surgery in the sheep model [ 32 ]. However, clinical experiments are required to confirm the safety and accuracy of this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that this new robotic-assisted TKA system significantly improve the accuracy of bone resection levels and angles in the Sawbone model [ 33 ]. Moreover, we demonstrated that this new system is a safe and accurate tool for TKA surgery in the sheep model [ 32 ]. However, clinical experiments are required to confirm the safety and accuracy of this system.…”
Section: Discussionmentioning
confidence: 99%
“…Our system also uses the CT data of lower limb to perform the preoperative plan and three -dimensional planning to orientate and size and actively uses the robotic arm to cut the bone and place for components. We previously investigated the accuracy and safety of this system in a sheep model and found that it might be an accurate and safe tool for TKA [ 32 ]. Moreover, we found that the accuracy of all of the bone resection levels was below 0.6 ​mm and all of the bone resection angles were below 0.6° in the HURWA robotic-assisted TKA group [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Several robot-assisted TKA (RA-TKA) systems have been approved by the National Medical Products Administration of China. [17][18][19] In this study, we utilised the RA-TKA system used in our previous research (Hangzhou Jianjia Robot Co. Ltd.) 3 for data collection and conducted a retrospective study to determine if RA-TKA was superior to conventional TKA (CON-TKA) in the following aspects: (1) the radiological parameters used to measure the rotation of the femoral and tibial components, (2) functional results based on the Knee Society Score (KSS), and (3) visual analogue scale (VAS) scores. We compared and analysed the radiographic and clinical outcomes of RA-TKA and CON-TKA using rotation angles, KSSs, and VAS scores as the primary evaluation indicators.…”
Section: Introductionmentioning
confidence: 99%